RESERVOIR CHARACTERIZATION WITH PETROPHYSICAL ROCK TYPE ANALYSIS AT RESERVOIR 2145ÃâÃâSD, BEKASAP FORMATION, SABAK FIELD IN CENTRAL SUMATRA BASIN - - NIM: 22014010, IRHAMI
Sabak Field is an oil field located in the eastern edge of Central Sumatra Basin, Riau. One of reservoir which produces hydrocarbons in this field is reservoir 2145’sd on Bekasap Formation. Reservoir characterization Sabak Field in more details is one of efforts needed to contribute to Sabak Field’s further development. The main data used in this study is core data and log data. Core data in this study can be found in well S-02 dan well S-4, while log data can be found in 27 well which is consisted of gamma ray log, resistivity log, density log, and neutron log. The data are processed and analyzed used core analysis, electrofacies analysis, petrophysic analysis and rock type analysis. The result from core analysis obtained six litofacies in this field. That litofacies consists of several types, including: (1) mudstone and siltstone (F), (2) very fine sandstone (Svf), (3) fine-medium sandstone (Sfm), (4) medium sandstone (Sm), (5) medium-coarse sandstone (Smc), (6) medium-coarse glauconitic sandstone (Smcg). Based on integration of core analysis and electrofacies analysis, this litofacies can be grouped into different facies associations, which are: (1) fluvial - tidal channel facies, (2) tidal sandbar facies, (3) mud flat facies. Rock type analysis is processed used method Flow Zone Indicator (FZI). This method uses Routine Core Analysis (RCAL) which only can be found in well S-02 and well S-04. The result of rock type analysis obtained reservoir 2145’sd can be grouped into three rock type (RT). RT 1 is the best rock type to flow fluid and RT 3 is the worst rock type to flow fluid. RT 1 consists of litofacies medium-coarse sandstone (Smc), medium sandstone (Sm), and very fine sandstone (Svf). RT 2 consists of litofacies fine-medium sandstone (Sfm), very fine sandstone (Svf), and medium-coarse glauconitic sandstone (Smcg). RT 3 consists of litofacies mudstone and siltstone (F) and very fine sandstone (Svf).